Powerful devices: prayer and the political praxis of spiritual warfare - Adelakun, Abimbola (Rutgers University Press, 2022)
Powerful Devices studies spiritual warfare performances as an apparatus for disestablishing structures of power and knowledge, and establishing righteousness in their stead. Drawing on performance studies’ emphasis on radicality and breaking of social norms as devices of social transformation, the book demonstrates how Christian groups with dominant cultural power but who perceive themselves as embattled wield the ideas of performance activism. Combining religious studies with ethnography, Powerful Devices explores Nigerian Pentecostals and US Evangelicals’ praxis of transnational spiritual warfare. By closely studying spiritual warfare prayers as a “device,” Powerful Devices shows how the rituals of prayer enable an apprehension of time, paradigms of self-enhancement, and the subversion of politics and authority. A critical intervention, Powerful Devices explores charismatic Christianity’s relationship to science and secular authority, technology and temporality, neoliberalism, and reactionary ideology